Thromboelastography in the setting of acetaminophen-induced hepatotoxicity. (4th May 2022) - Mohan, Sanjay; Koziatek, Christian; Swartz, Jordan; Howland, Mary Ann; Su, Mark K.
Abstract: Background: Severe acetaminophen (APAP) poisoning can result in fulminant hepatic failure and abnormal tests of coagulation. Although the international normalized ratio (INR) may be elevated, the actual hemostatic status of patients with APAP-induced hepatotoxicity is unknown. Few studies exist investigating the clinical use of thromboelastography (TEG) to evaluate the hemostatic status in the setting of APAP-induced hepatotoxicity. Methods: We performed a retrospective review of patients who were admitted for APAP toxicity and received TEG testing at a single transplant center. Results: Nine patients had detectable APAP concentrations and exhibited elevated aspartate and alanine aminotransferase activities. Seven had thrombocytopenia. TEG revealed a decreased median alpha angle and maximum amplitude but other values were within the normal reference range. Discussion: Based on our study of APAP-induced hepatotoxicity, TEG showed a decreased rate of fibrin formation and cross-linking, as well as reduced clot strength. These findings suggest that patients with APAP-induced hepatotoxicity and thrombocytopenia have a theoretically increased bleeding risk as demonstrated by both elevated INR and abnormal TEG values. However, these TEG findings are more likely related to thrombocytopenia rather than directly to APAP-induced hepatotoxicity. Further studies should be performed to elucidate the potential role of TEG in various stages of APAP-induced hepatotoxicity.